DYNAMIC TESTING SYSTEM DIAGNOSTICS - HENNEN, James; KUGEL, Ian; CARLSON, Kevin; THURMES, Kevin; BYRON, Tom (2025)
A dynamic testing system includes a test station and at least one controller. The test station includes a hydraulic actuator configured to drive an actuation of a test subject using a hydraulic fluid flow, and a control valve that includes a housing, a valve body contained within the housing having a position that controls a flow rate and direction of the hydraulic fluid flow, a valve body driver configured to adjust the position of the valve body based on a reference signal, and a valve position sensor configured to output a position signal that is indicative of the position of the valve body. The at least one controller is configured to obtain a current position of the valve body using the position signal, obtain a diagnostic reference, detect a diagnostic condition based on a difference between the current position and the diagnostic reference, and generate a diagnostic signal.